A Rare and Fatal Case of Bilateral, Upper, Lower Limbs and Abdominal Gangrene Linked to Brucellosis - Tejashree Anantha; Vidyavathi B. Chitharagi; M. Krishna Karthik; Jagadeesh Kumar; B. Sukesh Kumar; Badveti Satya Sai (Microbiology and Biotechnology Research: An Overview Vol. 1, 2025)
Brucellosis is one of the most commonly encountered zoonotic diseases predominantly caused by Brucella melitensis, Brucella abortus, and Brucella suis, with an estimated incidence of 5 lakh new cases/year. Brucellosis distributed worldwide is a classical zoonotic disease. Complications associated with gangrene are quite uncommon and may or might not occur during the course of the disease. Here, the case of a pediatric age group patient who presented with fever and gangrene over the upper and lower limbs and abdomen associated with brucellosis was presented. The patient had an antibody titer of 1:1280. Hence, routine serological diagnosis in patients with clinical signs and symptoms suggestive of brucellosis is essential. This also helps in detecting more number of cases. It was concluded that brucellosis still remains a serious threat and poses a severe impact on public health concerns, particularly where the disease is endemic. Hence, a high index of suspicion is really necessary when patients present with unexplained symptoms, especially for those who are at an occupational risk for brucellosis.